Arrest of Descent in the Second Stage of Labor – Incidence, Labor Outcomes, and Predictors of Cesarean Section: A Retrospective Case–Control Study in a Secondary Care Setting - Tobey Ann Marcus; D. Anita Shirley; Shalini Jeyapaul; Venkata Raghava Mohan; Anne George Cherian (Current Medical Issues)
Background: Arrest of descent is the failure of active descent of the fetal head in the second stage for over 1 h, resulting in either an instrumental delivery or a second-stage cesarean section (CS) which is known to be associated with increased maternal and perinatal complications. Methodology: The delivery records of 18,508 women were retrospectively reviewed. The objective of the study was to estimate the incidence, determine predictors of the arrest of descent in the second stage of labor, compare outcomes of deliveries with and without the arrest of descent, and outline predictors for CS. Women with singleton vertex pregnancy and unscarred uterus who had the arrest of descent in the second stage of labor were cases (n = 123) and controls (in a ratio of 1:2) were women who delivered vaginally without the arrest of descent. Birth data and outcomes were entered into Excel and analyzed using SPSS v 24.0. Results: There were 816 women, who had an arrest of descent in the second stage of labor (44 per 1000 births). Nulliparity (P < 0.001, odds ratio [OR]: 4.6), prelabor rupture of membranes (P = 0.002, OR: 2.2), birth weight >3000 g (P = 0.003, OR: 2.0), pelvic assessment showing doubtful adequacy (P < 0.001, OR: 24.08), and the presence of large caput (P < 0.001, OR: 4.453) were found to be significantly associated with arrest of descent. Complications such as postpartum hemorrhage (P < 0.001, OR: 3.568), postnatal fever (P < 0.001, OR: 3.693), and neonatal intensive care unit admission (P < 0.001, OR: 2.242) were significantly higher in the cases. Logistic regression was done to determine predictors of cesarean delivery and the presence of a large caput was the only significantly associated factor (OR: 6.429, P = 0.002). Conclusion: These findings can be used to facilitate early decision-making about the mode of delivery in women with arrest of descent, and early specialist involvement, particularly in low-resource settings.